2006
DOI: 10.1111/j.1365-2141.2006.06409.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion prevents acute chest syndrome predicted by elevated secretory phospholipase A2

Abstract: SummaryAcute pulmonary injury is known as acute chest syndrome (ACS) in patients with sickle cell disease (SCD). Secretory phospholipase A 2 (sPLA 2 ) was found to predict those at risk for ACS and a trial was designed to determine if red blood cell transfusion can be used to prevent ACS. Patients with an elevated sPLA 2 were randomised to either receive a single transfusion or standard care. Five of the eight patients (63%) randomised to standard care developed ACS versus none of the seven patients randomised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 7 publications
0
58
0
Order By: Relevance
“…Activated sPLA2 converts marrow fat into inflammatory free fatty acids that cause lung injury. Based on these observations, a small study evaluated the efficacy of prophylactic blood transfusions in patients with sPLA2 elevation during VOC (41). This therapeutic approach eliminated ACS in this very small cohort, suggesting that larger confirmatory trials are indicated.…”
Section: Acute Chest Syndromementioning
confidence: 99%
“…Activated sPLA2 converts marrow fat into inflammatory free fatty acids that cause lung injury. Based on these observations, a small study evaluated the efficacy of prophylactic blood transfusions in patients with sPLA2 elevation during VOC (41). This therapeutic approach eliminated ACS in this very small cohort, suggesting that larger confirmatory trials are indicated.…”
Section: Acute Chest Syndromementioning
confidence: 99%
“…One small prospective study demonstrated that RBC transfusion provided to patients hospitalized for pain who had elevated secretory phospholipase A2 levels helped to prevent ACS. 25 However, a subsequent clinical trial within the SCD Clinical Research Network designed to confirm these findings was closed due to inadequate subject accrual and poor predictive performance of secretory phospholipase A2.…”
Section: Acute Chest Syndromementioning
confidence: 99%
“…In a study of 14 adolescents, secretory phospholipase A 2 was used as a biomarker for ACS in patients hospitalized for vaso-occlusive crises. Early red blood cell transfusion prevented the development of ACS in these patients [55]. …”
Section: Sickle Cell Diseasementioning
confidence: 99%